"COVID-19 associated divergent thrombotic thrombocytopenic purpura (TTP) syndromes reported so far, five and counting": Classification and possible therapeutic options. Issue 219 (November 2022) - Mir, Tajamul H.
Highlights: The thrombotic complications of Covid 19 have posed a major therapeutic challenge to the clinician especially in critically ill. Besides the classic COVID-19 coagulopathy, a few cases of the thrombotic microangiopathy thrombotic thrombocytopenic purpura (TTP) have been reported as well following severe SARS CoV-2 infection. TTP, in the light of COVID-19, seems to be a mixed bag of different syndromes rather than a single entity requiring intense research, understanding, and timely recognition of these syndromes. A germane therapeutic approach could positively influence the outcome in these COVID-19 associated TTP syndeomes.